2020
DOI: 10.1038/s41467-020-18322-x
|View full text |Cite
|
Sign up to set email alerts
|

Gold catalysts containing interstitial carbon atoms boost hydrogenation activity

Abstract: Supported gold nanoparticles are emerging catalysts for heterogeneous catalytic reactions, including selective hydrogenation. The traditionally used supports such as silica do not favor the heterolytic dissociation of hydrogen on the surface of gold, thus limiting its hydrogenation activity. Here we use gold catalyst particles partially embedded in the pore walls of mesoporous carbon with carbon atoms occupying interstitial sites in the gold lattice. This catalyst allows improved electron transfer from carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 70 publications
(89 reference statements)
2
51
0
Order By: Relevance
“…It is interesting to note that at the time of this manuscript preparation, there was a recent paper depicting interstitial C insertion to modify coinage Au catalysts. 65 Our future work will explore further the structure and activity relationships of a wide range of interstitial ions or atoms in transition metal lattices combined with atomic scale spectroscopic techniques to see their catalytic impacts on chemical conversions. 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that at the time of this manuscript preparation, there was a recent paper depicting interstitial C insertion to modify coinage Au catalysts. 65 Our future work will explore further the structure and activity relationships of a wide range of interstitial ions or atoms in transition metal lattices combined with atomic scale spectroscopic techniques to see their catalytic impacts on chemical conversions. 53 …”
Section: Resultsmentioning
confidence: 99%
“…However, the doping does not appear to be only on Ag surface (Li ion effect is far stronger than other alkali ions) as the catalytic performance highly depends on the cationic size of alkali metal ions used. 65 Our future work will explore further the structure and activity relationships of interstitial ions or atoms of wide range of nature in transition metal lattices with the combined with atomic scale spectroscopic techniques to see their catalytic impacts in chemical conversions. 53 Here, it would be of significant importance to rationalize the change in catalytic effect of Au NP by Li ions from interstitial sites from theoretical standpoints.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…Recently, Wan et al have reported that carbon can be interstitially doped into Au for selective hydrogenation of alkyne-based substrates. 40 Though the XRD did not reveal any lattice variation, they speculated that the location of carbon is at the interstitial sites, as reflected by the XPS and XANES ( Fig. 12a and b ).…”
Section: Catalytic Applicationsmentioning
confidence: 96%
“…In recent work on the Au– int C system, doping does not induce any appreciable change in diffraction. 40 Expansion or contraction due to substitutional modification is usually interpreted using Vegard's rule, 17 which states that the concentration of a substitutional dopant is linearly correlated with the variation in the lattice parameter. However, it should be noted that Vegard's rule does not have a sound theoretical basis, as is often admitted by literature, with many exceptions reported.…”
Section: Characterisationmentioning
confidence: 99%
“…The use of slab models, given their possibilities, accessibility, and moderate computational expenses, has become the de facto workhorse in the last two decades; particularly when modeling reactivity at high coverage regimes of the clean surfaces, [68][69][70] although lately the increased computational resources allowed studying situations at a low coverage, [71][72][73] and including also surface defects such as vacancies, [74][75][76] subsurface species, [77][78][79] surface atoms, [80][81][82] and so on. Notice that slab models also permit to represent regular defects, such as surface steps, see Figure 2(a), by using vicinal surfaces slab models, [83][84][85] allowing also chemical resolution studies on chiral surfaces.…”
Section: Exemplary Modelsmentioning
confidence: 99%